2017
DOI: 10.1523/jneurosci.1975-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Selectively Reorganizes Excitatory Inputs to Substantia Nigra Pars Compacta Dopamine Neurons

Abstract: Substantia nigra pars compacta (SNc) dopamine neurons and their targets are involved in addiction and cue-induced relapse. However, afferents onto SNc dopamine neurons themselves appear insensitive to drugs of abuse, such as cocaine, when afferents are collectively stimulated electrically. This contrasts with ventral tegmental area (VTA) dopamine neurons, whose glutamate afferents react robustly to cocaine. We used an optogenetic strategy to isolate identified SNc inputs and determine whether cocaine sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…DA neurons from the SNc can selectively modulate the information processed by different input nuclei. For example, the AMPA/NMDA ratio is decreased at the PPTg-inputs to SNc, whereas it is unchanged in the STN-inputs to SNc (Beaudoin et al 2018).…”
Section: Sncmentioning
confidence: 97%
See 2 more Smart Citations
“…DA neurons from the SNc can selectively modulate the information processed by different input nuclei. For example, the AMPA/NMDA ratio is decreased at the PPTg-inputs to SNc, whereas it is unchanged in the STN-inputs to SNc (Beaudoin et al 2018).…”
Section: Sncmentioning
confidence: 97%
“…A single exposure to drugs and in particular psychostimulants, also alter the activity of SNc DA neurons and play a role in the increased expression of behavior mediated by DA release in the DSt (Zahniser et al 1998;Wolf 1998). A recent study, using optogenetics, has highlighted changes in specific glutamatergic afferents onto SNc neurons following a single cocaine exposure (Beaudoin et al 2018). Whereas previous studies showed that a single exposure to cocaine increases EPSCs in the VTA but failed to find an effect in the SNc (Ungless et al 2001;Lammel et al 2011), this could be due to the use of non-specific electrical stimulation of SNc DA neurons excitatory inputs.…”
Section: Sncmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the analysis of the promoter-associated mark H3K4me3 in individual cells/tissues Woo et al 2017) highlighted a nominal enrichment of SNP heritability in brain tissues and neuronal cell lines. The highest enrichment was observed in substantia nigra, which plays an important role in reward and thus it may be related to the development of the dependence (Beaudoin et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Men have higher rates of risk of death from cocaine use in relation to women. 17 This is because adult males have a higher risk of heart attacks and consume higher doses of cocaine in search of adrenaline and altered states of consciousness. The adverse effects of cocaine use are clearly seen in the cardiovascular system, since they produce significant increases in heart rate, generate alterations in blood pressure and adversely affect the contractility of the left ventricle of the heart.…”
Section: Discussionmentioning
confidence: 99%